Draft Ninth Five Year Plan 1997-2002 and Annual Plan 1997-98 Vol.-II (Statistical Tables) Government of Madhya Pradesh - Planning Commission (Planning Commission, 1997)
Draft Ninth Plan (1997-2002) and Draft Annual Plan 1997-98 - Proposed Outlays Draft Ninth Plan (1997-2002) and Draft Annual Plan 1997-98 - Proposed Outlays Physical Targets for Ninth Plan and Annual Plan 1997-98 Draft Ninth Plan (1997-2002) Proposals for Programmes/Projects Statement Regarding Externally Aided Projects Draft Ninth Plan (1997-2002) and Draft Annual Plan 1997-98 Outlays - By Heads of Development-For District Plans Centrally Sponsored Schemes Draft Ninth Plan (1997-2002) and Draft Annual Plan 1997-98 - Basic Minimum Services - Outlay/Expenditure A Tribal Sub-Plan (TSP)-I Ninth Plan 1997-2002 and Draft Annual Plan 1997-98 - Financial Outlays : Proposals for1 TSP Special Component Plan for Scheduled Castes (SCP)-I Draft Ninth Plan 1997-2002 and Draft Annual Plan 1997-98 -Financial Outlays : Proposals for SCP for Scheduled Castes Draft Ninth Plan (1997-2002) and Annual Plan 1997-98 - Proposed Outlays Financial Outlays/Expenditure for Voluntary Sector.
Government of Madhya Pradesh, Planning, Economics and Statistics Department